Synchronous primary neoplasia in patients with oropharyngeal cancer: Impact of tumor HPV status. A GETTEC multicentric study. (January 2021) - Milliet, Florent; Bozec, Alexandre; Schiappa, Renaud; Viotti, Julien; Modesto, Anouchka; Dassonville, Olivier; Poissonnet, Gilles; Guelfucci, Bruno; Bizeau, Alain; Vergez, Sebastien; Dupret-Bories, Agnes; Garrel, Renaud; et al.
Highlights: p16 + OPSCC had a lower rate of SPN. Alcohol and tobacco were associated to increased risk of SPN. SPN were preferentially located in UADT, lung and esophagus. Patients with SPN were more frequently oriented to a palliative strategy. There was no difference of overall survival between patients with or without SPN. Abstract: Introduction: Patients with oropharyngeal squamous cell carcinoma (OPSCC) display a significant risk of synchronous primary neoplasia (SPN) which could impact their management. The aims of this study were to evaluate the risk and distribution of SPN in OPSCC patients according to their HPV (p16) status, the predictive factors of SPN and the impact of SPN on therapeutic strategy and oncologic outcomes. Material and methods: All OPSCC patients treated from 2009 to 2014 were included in this multicentric retrospective study. Univariate analyses were conducted using Chi-2 and Fisher exact tests. For multivariate analyses, all variables associated with a p ≤ 0.10 in univariate analysis were included in logistic regression models. Results: Among the 1291 patients included in this study, 75 (5.8%) displayed a SPN which was preferentially located in the upper aerodigestive tract, lung and esophagus. Comorbidity level (p = 0.03), alcohol (p = 0.005) and tobacco (p = 0.01) consumptions, and p16 tumor status (p < 0.0001) were significant predictors of SPN. In multivariate analysis, p16+ status was significantly associated with a lower risk of SPN (OR = 0.251, IC95% [0.133;0.474]). Patients with a SPN were more frequently referred for non-curative treatment (p = 0.02). In patients treated with curative intent, there was no impact of SPN on the therapeutic strategy (surgical vs. non-surgical treatment). We observed no overall survival differences between patients with or without SPN. Conclusion: P16 tumor status is the main predictive factor of SPN in OPSCC patients. This study provides crucial results which should help adapt the initial work-up and the global management of OPSCC patients.